The roles of tumour suppressor miRNAs in liver cancer progression / Nur Najwa Adlina Mohd Zaid ... [et al.] - Mohd Zaid, Nur Najwa Adlina; Mohd Hatta, Fazleen Haslinda; Mohd Mutalip, Siti Syairah; Mohamed, Ruzianisra; Ahmad Noorden, Mohd Shihabuddin (Faculty of Pharmacy, 2021)
Liver cancer is the third leading cause of cancer-related death worldwide. The most prominent type of liver cancer is hepatocellular carcinoma (HCC). One of the most significant factors that contribute to the formation of this cancer is the aberrant microRNA (miRNA) expression in the liver tissue. miRNA is a small non-coding RNA molecule that plays vital roles in various biological processes and has been demonstrated to be the important contributor to the development of liver cancer. miRNA can either act as an oncogenic miRNA or tumour suppressor miRNA depend either they promote or inhibit cancer development in liver cell. The understanding on the factors and molecular mechanism that promote this cancer formation and progression are not completely understood. Thus, this shortcoming will contribute to a lot of drawbacks to the effectiveness of current therapy. This review provides the significant correlation of the tumour suppressor miRNAs' roles in liver cancer development and describes the potential use of miRNA as biomarker and therapeutic RNA drug to treat cancer. Thus, the understanding of molecular mechanisms underlying the initiation and progression of HCC is critical for early diagnosis and developing a new therapeutic strategy.